A Demographic Analysis of Stunting Issues in Relation to The Individuals Antenatal Care Services - Baska, Dwie Yunita; Nugraheni, Diah Eka; Abdullah, Vera Iriani; Novadela, Nora Isa Tri; Bertalina (EMBRIO: Jurnal Kebidanan, 2025)
Quality prenatal examinations can aid in the early detection of nutritional issues and provide necessary interventions. The standard for Antenatal Care (ANC) in Indonesia has been established to include a minimum of six visits throughout pregnancy, with a focus on monitoring maternal and fetal health. This study analyzes the demographic factors of maternal age, parity, gestational age, and occupation in relation to the individuals' ANC services and the incidence of stunting. The design of this study is a case-control study (1:1) with a total sample size of 212. The results indicated that maternal age, parity, gestational age, and occupation correlated with the individuals' ANC services. Maternal age during pregnancy exhibited a significant relationship with individuals' ANC service (p equal 0.001; OR equal 4.71), parity (p equal 0.001; OR equal 6.11), maternal gestational age (p equal 0.002; OR equal 3.80), maternal occupation (p equal 0.001; OR equal 4.25), and individuals' ANC services (p equal 0.001) concerning the occurrence of stunting. It is recommended to prioritize the enhancement of ANC services according to established standards, including routine examinations, monitoring of fetal growth, provision of appropriate health Education during pregnancy, and support from skilled healthcare professionals, to prevent complications and stunting.